Strawberry production progress in Brazil - Fagherazzi A.F.* (2017)
Currently in Brazil about 4,300 ha are cultivated in strawberry, with an annual production of about 150,000 t. Strawberries are mainly grown under low tunnels and 'Camarosa' and 'Albion' are the main cultivars used. Even with incentives from food companies, the fresh market still represents more than 90% of the commercialization of the Brazilian strawberry. Future trends will include: the search for new cultivars allowing an increase in production and in fruit quality; higher use of bare root plants produced by Brazilian nurseries; an improvement of integrated production techniques and organic cultivation; increasing day-neutral cultivars allowing to extend harvest period to all over the year; change from the traditional cultural system to the soilless culture. Researches will also be more active with the development of new genetic breeding programs aiming at creating new cultivars adapted to different cultural areas. In this way, the future premises for the strawberry cultivation are positive, putting Brazil in the world spotlights together with other traditionally important producing countries.